Nepotisme dan Korupsi di Pemerintahan Dalam Perspektif Etika - Tingka Febry Tory; Rizkia Amelia Hanum (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This paper discusses the phenomenon of nepotism and corruption in government from an ethical perspective. Through literature analysis and case studies, this paper examines how nepotism and corruption violate ethical principles, undermine the integrity of government, and harm society. This paper identifies the various forms of nepotism and corruption that occur in government, and analyzes their negative impact on governance, efficiency, and justice. It also discusses the factors that drive nepotism and corruption, such as patronage culture, weak law enforcement, and lack of transparency. As a solution, this paper recommends several strategic steps to prevent and eradicate nepotism and corruption in government, such as strengthening the meritocracy system, increasing transparency and accountability, and ethics education for public officials. This paper is expected to contribute to raising awareness about the importance of ethics in government, as well as encouraging efforts to create a clean, fair and integrity government.